Mechanically induced alterations in chromatin architecture guide the balance between cell plasticity and mechanical memory - Scott, Adrienne K.; Rafuse, Michael; Neu, Corey P. (Frontiers in Cell and Developmental Biology, 2023)
Phenotypic plasticity, or adaptability, of a cell determines its ability to survive and function within changing cellular environments. Changes in the mechanical environment, ranging from stiffness of the extracellular matrix (ECM) to physical stress such as tension, compression, and shear, are critical environmental cues that influence phenotypic plasticity and stability. Furthermore, an exposure to a prior mechanical signal has been demonstrated to play a fundamental role in modulating phenotypic changes that persist even after the mechanical stimulus is removed, creating stable mechanical memories. In this mini review, our objective is to highlight how the mechanical environment alters both phenotypic plasticity and stable memories through changes in chromatin architecture, mainly focusing on examples in cardiac tissue. We first explore how cell phenotypic plasticity is modulated in response to changes in the mechanical environment, and then connect the changes in phenotypic plasticity to changes in chromatin architecture that reflect short-term and long-term memories. Finally, we discuss how elucidating the mechanisms behind mechanically-induced chromatin architecture that lead to cell adaptations and retention of stable mechanical memories could uncover treatment methods to prevent mal-adaptive permanent disease states.